PENGARUH PROMOSI PENJUALAN DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN DI KREMA KOFFIE - Sholihat, Apriwati; ", Rumyeni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The purpose of this research is how the influence of sales promotion and quality of service to purchase decisions in Krema Koffie.The type of this research is quantitative explanative, with a sample of 96 respondents. The samples of this research using accidental sampling method. This research was conducted by using multiple linear regression test, Hypothesis Testing, Determination Test, Validity, Reliability and Classic Assumption Test. The results showed that sales promotion partially has a value of sales promotion significance of 0,000 <0.05 (significant level of significance), and t arithmetic of 3.365. The quality of service partially has a significant value of 0.000 with t arithmeti 7.075. Simultaneously the significance value of the regression model is 0,000 with the value of f arithmetic of 52,699.The results showed that sales promotion and service quality have a positive and significant impact on purchasing decisions at Krema Koffie, even partially or simultaneously.Key word: Sales Promotion, Service Quality. Purchasing Decision